Intention to purchase wellbeing food among Korean consumers: An application of the Theory of Planned Behavior. (March 2021) - Lim, Hui-Rang; An, Soyoung
Highlights: Attitude toward purchasing Yak-sun food showed a positive relationship with behavioral intention. Subjective norm showed a positive relationship with behavioral intention of purchasing Yak-sun food. Perceived Behavioral Control found out to be the most influential factor on behavioral intention to purchase Yak-sun food. Abstract: Studies on consumers' purchase intentions have been one of the focuses in academia; however, the complex decision-making process in terms of purchase intentions on well-being foods have not been well researched. This study applied the Theory of Planned Behavior (TPB) model using its core constructs to predict consumers' purchase intentions of well-being food, namely Yak-sun . Questionnaires were gathered using a convenient sampling method for those who have experienced Yak-sun food in September of 2014. A total of 269 responses were used for data analysis. The results of the study aligned with past studies that supported the applicability of the TPB model. All constructs including attitude, subjective norms, and perceived behavioral control were found to have made a significant contribution to the prediction of intention to purchase Yak-sun food among Korean consumers. Perceived behavioral control showed the strongest influence on the behavioral intention of purchasing Yak-sun food. Based on the results, theoretical and practical implications were suggested.